PF.17 Fetal Biometry Revisited. (26th April 2013) - Khalid, A; Higgins, JR; McKenna, DJ
Abstract : Objective: To construct fetal biometric charts in the Irish population using methodology recommended by Altman and Chitty with up-to-date ultrasound equipment. Study design: This was a prospective, cross-sectional study involving low-risk women attending Cork University Maternity Hospital. Women were recruited from their first trimester dating scan and randomly allocated to a single scan between 14–40 weeks gestation. Scans were performed by a sole researcher. Gestation was calculated using the estimated-due-date (EDD) by dating scan. Recruits were Irish Caucasian women with a singleton pregnancy. Women with conditions affecting fetal size including hypertension, pre-eclampsia, renal disease, autoimmune disorders and diabetes mellitus were excluded as were fetuses with congenital anomalies. Biometrical measurements were performed using the Voluson E8 ultrasound by GE Healthcare. Results: Nine-hundred-and-fifteen women were recruited. Seven-hundred-and-ninety-three women met the inclusion criteria and were scanned as per protocol. Median maternal age was 32 (range 17–44). Median BMI was 24.7 (range 17.1–48.6). Nulliparous women constituted 46.5% (369/793) of recruits, 32.6% (261/793) were expecting their second child, 18.3% (145/793) were expecting their third or fourth child, while only 2.3% (18/793) were grand multiparous. Biometric charts for biparietal diameter (BPD), head circumference (HC), femur length (FL) and abdominal circumference (AC) have been generated for this population and compared to the biometric charts by Chitty et al, Following is a table showing calculated percentiles for BPD measurements in this population. Conclusion: We have constructed Irish Caucasian specific fetal biometry charts with up-to-date equipment using Chitty and Altman's methodology.